Spectrophotometric determination of β-blocker drugs by oxidation with bromate–bromide mixture and its analytical application to pharmaceutical preparations. Issue 6 (2011) - El-Didamony, Akram M.; Erfan, Eman A. H.
Abstract : Three visible spectrophotometric methods (A–C) were developed for the analysis of some β -blocker drugs, namely atenolol (ATE) and timolol (TIM) based on their reactivity with bromine, generated in situ by the action of hydrochloric acid on bromate–bromide mixture. The determination of residual bromine is based on its ability to bleach the indigo carmine dye and measuring the absorbance at 610 nm (method A). Methods B and C involve treating the unreacted bromine with a measured excess of iron (II), the remaining iron (II) is complexed with 1, 10-phenanthroline (method B) or with 2, 2'-bipyridyl (method C) and measuring the increase in absorbance at 510 and 522 nm, respectively. In all the methods, the amount of bromine reacted corresponding to the drug content. Regression analysis of Beer's plot showed good correlation in the concentration ranges of 0.4–16.4, 0.8–10.4 and 0.4–12.8 µg/ml using methods A–C, respectively, for ATE and 14–38, 12–32 and 14–38 µg/ml using methods A–C, respectively, for TIM. The optimum reaction conditions and other analytical parameters are evaluated. No interference was observed from the additives and the applicability of the methods was tested by analyzing the pharmaceutical preparations containing the investigated drugs. Statistical comparison of the results with those of official methods shows excellent agreement and indicates no significant difference in precision.